2015
DOI: 10.1097/aln.0000000000000605
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Ventilation Induces Neutrophil Extracellular Trap Formation

Abstract: NETosis was induced in VILI, and DNase treatment eliminated NETs. In contrast to experimental transfusion-related acute lung injury, NETs do not play a major pathogenic role in the current model of VILI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 39 publications
3
61
0
Order By: Relevance
“…We found that circulating extracellular DNA levels were similarly elevated in the three patient groups, independently of clinical severity. This concurs with the results of Yildiz et al [42] who found that mechanical ventilation induced netosis in an animal model of sepsis, but that netosis had no major pathogenic effect. However, netosis intensity has been linked to severity in two models of sterile ARDS: acid-aspiration-induced ARDS [43] and transfusion-related acute lung injury [44].…”
Section: Discussionsupporting
confidence: 93%
“…We found that circulating extracellular DNA levels were similarly elevated in the three patient groups, independently of clinical severity. This concurs with the results of Yildiz et al [42] who found that mechanical ventilation induced netosis in an animal model of sepsis, but that netosis had no major pathogenic effect. However, netosis intensity has been linked to severity in two models of sterile ARDS: acid-aspiration-induced ARDS [43] and transfusion-related acute lung injury [44].…”
Section: Discussionsupporting
confidence: 93%
“…In this murine model, mechanical ventilation plus LPS was associated with increased airway levels of HMGB-1 and IL-1β, and a tendency to increase the CCL2/MCP-1 and IL-6 concentrations. Noteworthy is that the authors showed that intratracheal DNase treatment reduced NET markers but did not significantly impact on different measures of injury, concluding that NET do not play a major pathogenic role in this model of VILI [57] . However, our findings, which indicated that MNase treatment did not reduce the cytokine-stimulatory capacity of MSU-induced NET, suggest that evaluation of this parameter is not enough to rule out a role of NET in pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that both UA and MSU induce NET formation [10,37] , our findings, which indicated that these NET markedly increased the production of proinflammatory cytokine by the airway epithelial cells, suggest that NET could contribute to the exacerbation of lung inflammation, not only upon bleomycin administration but also in ALI. Recent studies reported increased UA levels in lung lavage fluid in a murine ventilator-induced lung injury (VILI) model [23] , and demonstrated that mechanical ventilation, together with LPS instillation, induced NET formation [57] . In this murine model, mechanical ventilation plus LPS was associated with increased airway levels of HMGB-1 and IL-1β, and a tendency to increase the CCL2/MCP-1 and IL-6 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] However, more recent work has demonstrated that NETs also form in response to noninfectious tissue injury. 9,10 The depletion of NETs from injured lungs has been shown to inhibit pulmonary edema, promote microcirculation, and attenuate fibrosis. 9,10 The depletion of NETs from injured lungs has been shown to inhibit pulmonary edema, promote microcirculation, and attenuate fibrosis.…”
Section: Introductionmentioning
confidence: 99%